KESESUAIAN FUNGSI KAWASAN DENGAN PEMANFAATAN LAHAN DI DAERAH ALIRAN SUNGAI SAMIN TAHUN 2007 - Nugraha, Setya (MIIPS, 2008)
The research conducted in the watershed of Samin is aimed to find out the function of the land area, the exploitation of the land, and the compatibility of the function of the land area with its exploitation. The research method applied in this research was survey method, by using land unit as the analysis unit. The population was 152 land units. The samples were taken by using purposive sampling technique. The data were collected by direct field observation and from the documentation. The analysis technique of this research was descriptive qualitative. The result of the research shows that the exploitation for rice field was 48,63 %, settlement was 25,02 %, plantation was 11,12 %, non-irrigated field was 11,07%, bushes was 3,90% and river was 0,23%. The function of the Samin watershed area land consists of 10, 05 % shelter area function, 33,44% local shelter area function, 5,03% buffer area function, 5,05% perennial plants cultivation area function, and 46,42% seasonal plants cultivation area function and settlement. The exploitations of the actual area of Samin watershed which were improper with the function of land area were 10,05% in shelter area, 33,44% in local shelter area, 3,82% in buffer area, and 4,32% in perennial plants cultivation area.